Improving diagnosis of childhood arterial ischaemic stroke. (2nd December 2017) - Mackay, Mark T.; Monagle, Paul; Babl, Franz E.
ABSTRACT: Introduction : At least half of childhood stroke survivors suffer long-term impairments. Rapid identification of stroke is essential to minimize the extent of injury by restoring perfusion to viable brain. Improving diagnosis of childhood stroke requires correct identification of stroke by prehospital and emergency physicians, rapid performance of appropriate neuroimaging to confirm infarction, and targeted investigations to determine underlying causes, which guide treatment decisions to reduce recurrence risk. Areas covered : This review will summarize the barriers to rapid stroke diagnosis in pre-hospital and emergency department settings, describe recent progress in understanding of the spectrum, presenting clinical features and differential diagnosis of childhood stroke, discuss clinical stroke recognition tools which improve diagnostic accuracy, and their application to children. Recent advances in the diagnostic evaluation of stroke will be presented, and the review will conclude by outlining priorities for future research. Expert commentary : Development of coordinated systems of acute care are essential to facilitate rapid diagnosis of childhood stroke. Recent advances in acute pediatric stroke care include consensus recommendations for primary pediatric stroke centers and implementation of standardized Pediatric Code Stoke protocols, which result in shorter time to diagnosis, selection of MRI as the initial imaging modality, and increased access to reperfusion therapies.